Peran Pendapatan Asli Daerah, Dana Perimbangan dan Belanja Daerah Terhadap Kemiskinan - Rizki Ramadhani (Politeknik Raflesia Press, 2024)
This study examines in more depth the role of regional spending as an intervening variable in its influence on Local Revenue (PAD), Special Allocation Funds (DAK), and Revenue Sharing Funds (DBH) in reducing poverty levels. The study uses data samples from the Special Region of Yogyakarta from 2018 to 2023 with the analysis tool EViews 13. To ensure the role of regional spending as a mediating variable, the Sobel test was used. The results of the study found that regional spending is able to mediate the relationship between Local Revenue and Revenue Sharing Funds in reducing poverty levels. However, no mediating role of regional spending was found in the effect of Special Allocation Funds on poverty levels. Regional spending independently has a significant impact on poverty reduction.